FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA MENGIKUTI PELATIHAN BREVET PAJAK - Nur Kholis (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2018)
The purpose of this study to determine the influence of career motivation, knowledge taxation and perception of education costs of student interest following the training of taxation brevet. Sources of data used primary data and sampling techniques using purposive sampling with a total sample of 349 respondents The result of research of career motivation variable and tax knowledge variable have positive effect on the interest of Students following the training of tax brevet, while the educational cost negatively affect the student's interest to follow the training of tax brevet